Cancer Prevention Literacy among Different Population Subgroups: Challenges and Enabling Factors for Adopting and Complying with Cancer Prevention Recommendations - Sharp, Lena; Dodlek, Nikolina; Willis, Diane; Leppänen, Arja; Ullgren, Helena (My University, 2023)
It is estimated that 40% of the cancer cases in Europe could be prevented if people had better information and tools to make healthier choices and thereby reduce some of the most important cancer risk factors. The aim of this study is to gain knowledge and understanding about cancer prevention literacy among people with intellectual disabilities, immigrants, young people and young cancer survivors. In this qualitative study, we conducted six online focus-group interviews, including forty participants, to explore the cancer prevention literacy of four population subgroups and determine how cancer prevention recommendations according to the European Code Against Cancer (ECAC) were perceived. The analysis resulted in the following main categories: current health beliefs and their impacts on how the ECAC recommendations were perceived, communication strategies and sources benefiting or hindering cancer prevention information from reaching out, and how vulnerabilities in these subgroups impact cancer prevention literacy. To improve cancer prevention literacy in Europe, more attention is needed this topic to overcome barriers among different population subgroups. Recommendations include improved and adapted cancer prevention information, support to individuals, as well as societal support, such as easy-access screening and vaccination programmes and regulations related to tobacco, alcohol, and diet.
Keywords: cancer prevention; cancer prevention literacy; communication; health inequalities; health literacy; public health